Analysis of genetic diversity and selection characteristics using the whole genome sequencing data of five buffaloes, including Xilin buffalo, in Guangxi, China - Chen, Zhefu; Zhu, Min; Wu, Qiang; Lu, Huilin; Lei, Chuzhao; Ahmed, Zulfiqar; Sun, Junli (Frontiers in Genetics, 2023)
Buffalo is an economically important livestock that renders useful services to manhood in terms of meat, milk, leather, and draught. The Xilin buffalo is among the native buffalo breeds of China. In the present study, the genetic architecture and selection signature signals of Xilin buffalo have been explored. Correlation analysis of the population structure of Xilin buffalo was conducted by constructing NJ tree, PCA, ADMIXTURE and other methods. A total of twenty-five (n = 25) Xilin buffalo whole genome data and data of forty-six (n = 46) buffaloes published data were used. The population structure analysis showed that the Xilin buffalo belong to the Middle-Lower Yangtze. The genome diversity of Xilin buffalo was relatively high. The CLR, π ratio, FST, and XP-EHH were used to detect the candidate genes characteristics of positive selection in Xilin buffalo. Among the identified genes, most of the enriched signal pathways were related to the nervous system and metabolism. The mainly reported genes were related to the nervous system (GRM5, GRIK2, GRIA4), reproductive genes (CSNK1G2, KCNIP4), and lactation (TP63). The results of this study are of great significance for understanding the molecular basis of phenotypic variation of related traits of Xilin buffalo. We provide a comprehensive overview of sequence variations in Xilin buffalo genomes. Selection signatures were detected in genomic regions that are possibly related to economically important traits in Xilin buffalo and help in future breeding and conservation programs of this important livestock genetic resource.